Small spaces - Arden, Katherine (G.P. Putnam's Sons Books for Young Readers, 2018)
Eleven-year-old Ollie comes across a weeping woman next to a river, holding a book and threatening to throw it into the water. Ollie is impulsive, so she plucks the book from the woman's hand and runs off with it. The book is "Small Spaces," and tells a haunting story of a girl, two boys in love with her, and a farm from hundreds of years ago, and a deal with the sinister specter called the Smiling Man, who grants wishes for the ultimate price. Now, Ollie finds herself on a school trip to a local farm with a haunted history.